Aligning Cytology, Histopathology, and Surgical Choices: A 10 Year Review of Thyroid Nodule Management at the University Clinical Center of Kosovo - Rinё Limani; Shkelzen Reçica; Etnik Bajraktari; Zgjim Limani; Arbnora Shaqiri; Fisnik Kurshumliu; Labinota Kondirolli; Fatlinda Sadiku; Brikenё Blakaj Gashi; Drita Miftari Pazhari (International Journal of Biomedicine)
Thyroid nodules are detected in up to 60% of individuals by high-resolution ultrasonography, yet only a small proportion prove malignant, with papillary thyroid carcinoma being the most common. Fine-needle aspiration cytology (FNAC) is the primary, minimally invasive, and cost-effective method to triage nodules for surgery. The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) standardizes FNAC interpretation into six categories with associated malignancy risks. However, indeterminate categories Bethesda III (AUS/FLUS) and IV (follicular neoplasm/suspicious for follicular neoplasm) present diagnostic challenges, exhibiting malignancy rates from 5% to over 30%, influenced by institutional practices and follow-up protocols. Sampling technique, slide preparation, and diagnostic experience further affect consistency. In Kosovo, where molecular testing is yet largely unavailable, FNAC remains the sole preoperative tool. The rise in incidentally detected sub-centimeter nodules, many of them low-risk microcarcinomas, complicates management in settings where surveillance is unreliable, often leading to overtreatment. Although current guidelines now endorse active surveillance and adjunctive molecular markers for indeterminate lesions, these tests are cost-prohibitive in resource-limited regions. This study leverages the unique position of our academic center to conduct a 10-year retrospective analysis of over 1800 FNACs and 1000 surgical cases, aiming to validate local FNAC performance, refine risk stratification, and inform context-appropriate management pathways.